Development of Listening Comprehension Learning Media for Beginners-Based Websites - Risnovita Sari; Rina Evianty (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research is entitled Development of Website-based Listening Comprehension Learning Media for Beginners. The purpose of this research is to produce a product, namely the learning media of the E-learning website. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). In the analysis phase, a preliminary study, curriculum analysis, and needs analysis are carried out. At the design stage, an outline of the contents of the website and the preparation of the website framework are made. At the Development stage, website creation, website packaging and presentation, quiz design, testing by media experts and material experts are carried out. At the implementation stage, tests were carried out on small classes and large classes. The evaluation stage includes indicators of media success which quantity evaluates each stage of development. The application used for this development is Adobe after Effects.